Microsoft Dynamics CRM 2011 cookbook : includes over 75 incredible recipes for deploying, configuring, and customizing your CRM application /: includes over 75 incredible recipes for deploying, configuring, and customizing your CRM application. (2013) - Bhattacharya, Dipankar
No abstract available